Insulin‐like growth factor binding protein 7 accelerates hepatic steatosis and insulin resistance in non‐alcoholic fatty liver disease. (29th August 2019) - Yan, Hua; Li, Ting; Wang, Yatao; Li, Hong; Xu, Jingyuan; Lu, Xiaolan
Abstract: An association between increased insulin‐like growth factor binding protein‐7 (IGFBP7) expression and insulin resistance in metabolic diseases has been reported. However, the role and molecular mechanism of IGFBP‐7 in non‐alcoholic fatty liver disease (NAFLD) remains largely unknown. Therefore, the potential function of IGFBP7 in the pathological progression of NAFLD was explored in this investigation. For in vivo experiments, an animal model of NAFLD was established in C57BL/6 mice by feeding a high‐fat diet (HFD), and IGFBP7 was knocked down by injecting adeno‐associated adenovirus (AAV)‐mediated short‐hairpin (sh)‐IGFBP7 into the liver. We found that AAV‐sh‐IGFBP7 treatment significantly alleviated hepatocyte injury and inhibited hepatic lipid accumulation by reducing lipogenesis‐associated gene expression. Furthermore, downregulation of IGFBP7 markedly ameliorated IR and restored impaired insulin signalling by elevating the phosphorylation levels of IRS‐1, Akt and GSK3β in HFD‐treated mice. Similar results were also confirmed by an in vitro study in a palmitic acid (PA)‐stimulated HepG2 cell model. In conclusion, our study demonstrates that IGFBP7 contributes to hepatic steatosis and insulin resistance in NAFLD development, which might serve as a novel therapeutic agent for the treatment of NAFLD.